ANALISIS MEDIA SOSIAL INSTAGRAM MAL BOTANI SQUARE DALAM MEMPROMOSIKAN EVENT - Riswanda, Rifa; Syah, Firman (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2025)
Instagram has become one of the most effective digital marketing tools for shopping malls, including Botani Square Mall. This study aims to analyze the effectiveness of Instagram in enhancing customer engagement and supporting the marketing strategy of Botani Square Mall. The research method used is descriptive analysis with a qualitative approach, which includes observations of Botani Square Mall's Instagram content, user interactions, and interviews with social media managers.The research results show that the use of interactive features Reels increases Instagram engagement at Botani Square Mall. Moreover, consistency in posting content and the use of attractive visual strategies also play a role in enhancing audience appeal. In conclusion, Instagram is an effective platform for supporting the promotion of Botani Square Mall, provided that content strategies are continuously adapted to trends and customer preferences.